Dynamic model of infectious diseases on the coronavirus disease 2019 - Bin Zhao; Junjie Liu; Ke Wang; Zhiyong Deng; Jinming Cao (Annals of Mathematics and Physics - Peertechz Publications, 2020)
In order to find out and predict the impact on the spread of infectious diseases, we established a class of kinetic models, gave formulas for calculating numbers, analyzed inflection points and predicted the development trend of new coronaviruses, and used C0VID-19 as an example for numerical simulation . Background: In December 2019, China's first unexplained pneumonia patient was admitted to Wuhan Jinyintan Hospital, Hubei, China. Since then, COVID-19 has expanded rapidly in Wuhan, Hubei, China. Within a few months, COVID-19 soon It spread to 34 provincial administrative regions and neighboring countries across China, and Hubei Province immediately became the hardest hit by the new coronavirus. New coronavirus pneumonia (COVID-19) As of April 17, 2020, the cumulative number of confirmed cases in China was 83,824, the cumulative number of deaths was 3352, the cumulative number of foreign diagnoses was 2,090000, and the cumulative deaths were 141,601. The outbreak and spread of COVID-19 have seriously affected people's Good health has caused huge economic losses in our country. It is of far-reaching significance to explore effective prevention and control of infectious diseases and minimize the harm caused by infectious diseases. In an emergency situation, we strive to establish an accurate infectious disease dynamic model to predict the development and spread of COVID-19, and make some effective short-term predictions on this basis. The construction of this model is relevant to all aspects of mainland China. It is helpful for the department to carry out the prevention and monitoring of the new coronavirus. It also strives for more time for the clinical trials of Chinese researchers and the research of vaccines against the virus to eliminate the new coronavirus as soon as possible. Methods: Collect and compare and integrate the spread of COVID-19 in Hong Kong, record the spread of the virus in the population and the protest measures of relevant government departments, and establish a dynamic model of infectious diseases based on the original data changes. Interpretation: In the early stage of the epidemic, due to inadequate anti-epidemic measures, the epidemic in Hong Kong quickly spread. However, with the gradual understanding of COVID-19, the epidemic began to be gradually controlled, and then the growth was blocked.